Parental Investments and Children's Human Capital in Low-to-Middle-Income Countries - Behrman, Jere R. (Cambridge University Press, 2024)
This Element reviews what we know about parental investments and children's human capital in low-to-middle-income countries and finds different patterns, often weaker relations, than associational studies. This title is also available as Open Access on Cambridge Core.